Pengembangan Sumber Daya Pegawai Sekolah Tinggi Manajemen Informatika dan Komputer Adhi Guna Palu Sulawesi tengah - Saiful Saiful; Mohammad Andika (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the process of developing employee human resources at the College of Informatics and Computer Management Adhi Guna Palu, Central Sulawesi. By taking the approach 1. Education 2. Training and 3. Development. The research method used is Descriptive Qualitative, namely by describing conditions according to what happened, Observation Data collection techniques, Interviews and Literature Studies. The results of the study based on 3 (three) aspects of the first study show that education has been carried out well, employees who wish to continue their education are given the opportunity to continue their education. Both trainings are provided with the aim that employees can update related to developments in accordance with their field of work. Third, employee development aims to enable employees to be promoted to occupy certain positions within the Adhi Guna STMIK scope.